Eligibility for mechanical circulatory support devices based on current and past randomised cardiogenic shock trials. (16th August 2021) - Schrage, Benedikt; Beer, Benedikt N.; Savarese, Gianluigi; Dabboura, Salim; Yan, Isabell; Sundermeyer, Jonas; Becher, Peter M.; Grahn, Hanno; Seiffert, Moritz; Bernhardt, Alexander; Thiele, Holger; Møller, Jacob E.; et al.
Abstract : Aims: Mechanical circulatory support devices (MCS) are potentially effective treatments for cardiogenic shock (CS) and are thus evaluated in several randomised controlled trials (RCTs). However, it is not clear how enrolment criteria of these RCTs apply to a real‐world CS population. This study aimed to shed light on eligibility to these trials. Methods and results: Pragmatic enrolment criteria for the IABP‐SHOCK II, the DanGer‐SHOCK, the ECLS‐SHOCK and the EURO‐SHOCK trials were retrospectively applied to 1305 CS patients admitted to a tertiary care hospital between 2009 and 2019. Based on this, major enrolment criteria were identified and outcome between eligible and ineligible patients was assessed. In this study, 415 (31.8%) patients were eligible for any study. Lowest eligibility was observed for DanGer‐SHOCK (11.9%) and the highest for IABP‐SHOCK II (26.9%). Over all trials, inclusion criteria were more restrictive than exclusion criteria and absence of CS caused by acute myocardial infarction (AMI) was the primary reason for non‐eligibility. However, even in CS caused by AMI, enrolment criteria were only met in 65.4% of patients. Importantly, 30‐day mortality was high across all patients/trials, irrespective of eligibility or non‐eligibility. Conclusion: The present study highlights that current and past RCTs only reflect about a third of the overall CS population. While enrolment criteria are a necessary aspect of RCTs, their application limits generalisability of the trials' findings. More trials on CS sub‐populations not represented by current or past trials, e.g. CS not caused by AMI, are needed, especially as mortality is high irrespective of eligibility status.